The Notion of the Recognition of Territorial Acquisition - Wiewióra, Bolesław (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The paper is an English translation of Uznanie nabytków terytorialnych w prawie międzynarodowym by Bolesław Wiewióra, published originally in Polish in 1965. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Department of Public International Law” devoted to the achievements of the representatives of the Poznań studies on international law.